1800 years of encounters with Mandaeans - Buckley, Jorunn Jacobsen (Gorgias Mandaean Studies, 2023)
"Jorunn Jacobsen Buckley's new book is both an updated academic study and an autobiographical account of her decades-long Mandaean encounters. The book includes the author's intellectual timeline in Mandaean studies from the late 1960s until today, a study of Mandaean scribal lineages, accounts of private and public meetings with Mandeans around the world with 26 anecdotes / vignettes, as well as selections from a privately printed book on her international human rights work for Mandaeans. The book is dedicated to a treasured Mandaean friend, the yalufa (learned layman) Sh. Salem Choheili"--